The Role of Intestinal Dysbacteriosis Induced Arachidonic Acid Metabolism Disorder in Inflammaging in Atherosclerosis - Sun, Yingxin; Wu, Danbin; Zeng, Wenyun; Chen, Yefei; Guo, Maojuan; Lu, Bin; Li, Huhu; Sun, Chun; Yang, Lin; Jiang, Xijuan; Gao, Qing (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Ageing inducing chronic systemic inflammatory responses is an important risk factor for atherosclerosis; however, the detailed mechanism is still to be elucidated. Objective: To explore the underlying mechanism between ageing and AS advancement based on the association study between intestinal flora and serum metabolites. Methods: Young (five-week-old) and elderly (thirty-two-week-old) male apolipoprotein E-deficient mice were used in this study. After 32 weeks diet intervention, size of AS lesion, the serum levels of lipid; inflammatory cytokines and LPS were analyzed. We then used an integrated approach combining 16S rRNA sequencing and Serum metabolomics profiling to examine the functional impact of the interactions on the AS. Results: Ageing apolipoprotein E-deficient mice suffered from more severe AS lesion and low-grade systemic inflammation. Besides, an increasing level of serum LPS, a decreasing level of SCFAs production, as well as a dysfunction of ileal mucosal barrier were detected in ageing mice. 16S rRNA sequencing revealed that there were significant differences in the intestinal flora composition between YM and OM groups. Moreover, metabolomics profiling revealed a concurrent effect, and 20-HETE, PGF2α, Arachidonic acid, LTB4 belonging to the arachidonic acid (AA) metabolic pathway were identified. These suggest that metabolic abnormalities and disorders of intestinal flora occurred in AS mice. Conclusions: Ageing not only alters the gut microbiome community but also substantially disturbs metabolic condition. Our results confirm that AA metabolism is associated with intestinal flora in AS lesions of aging. These findings may provide novel insights regarding gut flora disorders and gut microflora–related metabolites induced inflammaging as a potential new mechanism by which ageing leads to or exacerbates AS.